Konflik dalam Transportasi Angkutan Kota Di Kota Malang = Conflict in Urban Transportation in Municipality of Malang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Nowadays transportation plays a central role in urban life. The dependence of urban life on transportation is increasingly greater. This is caused by people's increasing need to travel, their improving economic conditions, and population growth as well as the more specialized and extended fungction of land in the cities, which require the support of adequate transportation facilities and infra-structure to ensure effective and efficient mobility of city people in doing their activities. The operation of urban transportation involves many parties such as policy makers, financiers (related to the provision of vehicles), owners, drivers and passengers, all of whom have their own interests. Any failure to reconcile these interests is likely to result in a conflict of interests. This research seeks to find out the situation of conflict that arises in the operation of urban transportation in the municipality of Malang. This research was conducted in the municipality of Malang, adopting a descriptive qualitative method. Data collection was carried out through interviews and a documentary study. Primary data were obtained directly from drivers and passengers as well as from the mass media, particularly with regard to historical information. Secondary data were obtained from key informants, some of whom were the DLLAID (the local traffic and road transportation service). The data were analyzed qualitatively by describing the phenomena related to the operation of urban transportation and conflict behavior. Results of data analysis were interpreted by giving significance to the exiting phenomena. The research findings are as follows: 1) the conflicts that arise in the operation of public transportation are caused by political and economic interest